Development of a Maritime Safety - Tool for Inner Harbour Ferry Transport Operations - KERSHAW, Carl; KLOCKNER, Karen (Transactions of the VŠB-Technical University of Ostrava, Safety Engineering Series, 2021)
This research was interested in examining if an existing rail industry accident investigation tool could be modified for inner harbour ferry operations. The Contributing Factors Framework (CFF) investigation tool was therefore modified for the maritime industry, specifically as both an investigation tool and a post safety occurrence coding tool. The outcome of this research was the development of a new practical human factors centred investigation tool. It provides a framework for the identification of complex sociotechnical system failures and contributing factors specific to inner harbour ferry operations. The new Contributing Factors Framework-Maritime Safety (CFF-MS) tool fills an existing gap in the need to be able to identify specific inter-relationships between people, technology, and the wider transport system when conducting maritime industry safety investigations.